Exponential Admissibility and H∞ Control of Switched Singular Time-Delay Systems: An Average Dwell Time Approach - Jinxing Lin; Zhifeng Gao (Journal of Applied Mathematics)
This paper deals with the problems of exponential admissibility and H∞ control for a class of continuous-time switched singular systems with time-varying delay. The H∞ controllers to be designed include both the state feedback (SF) and the static output feedback (SOF). First, by using the average dwell time scheme, the piecewise Lyapunov function, and the free-weighting matrix technique, an exponential admissibility criterion, which is not only delay-range-dependent but also decay-rate-dependent, is derived in terms of linear matrix inequalities (LMIs). A weighted H∞ performance criterion is also provided. Then, based on these, the solvability conditions for the desired SF and SOF controllers are established by employing the LMI technique, respectively. Finally, two numerical examples are given to illustrate the effectiveness of the proposed approach.